Adult heart procurement following circulatory determined death from a donor on venous-venous extracorporeal membrane oxygenation: A case report. (March 2023) - Nachum, Eyal R; Hogan, John; Osman, Mohamed; Messer, Simon; Baxter, Jennifer; Olano, Francisco; Berman, Marius; Large, Stephen
Donation after circulatory death in the context of heart transplants is attracting interest and becoming popular in clinical practice. Activity is growing in the United Kingdom, Australia, and the United States. We believe that a prolonged warm ischemic time (time from asystole to reperfusion of the heart on an ex vivo perfusion system) is a primary indicator of adverse outcomes. However, 1.5 liters of blood must be retrieved from the right atrium following sternotomy prolonging warm ischemic time. The patient in the following case report was supported by veno-venous extra-corporeal membrane oxygenation following drowning, further complicated by aspiration-related lung failure. Following circulatory death and a mandatory five-minute stand-off period, 1.5 liters of blood was drained from the circuit as sternotomy began. Surgeons then proceeded to direct procurement of the heart, aiming for least functional warm ischemic time. Following standard implantation, the patient's postoperative recovery has been unremarkable to date.